Performance of dairy animals in commercial dairy farms in Karnataka - M.C., Sathisha; Tiwari, Rupasi; Roy, Rakesh (Indian Journal of Dairy Science, 2018)
Karnataka has been purposively selected due to its status as leading producer of milk and commercial dairy farming is in developing stage as compared to other states of the Southern India. In all, 135 respondents from 3 districts form the total sample size for the study having equal representation of small (10-20 milch animals), medium (21-40 milch animals) and large (>40 milch animals) commercial dairy farmers. The study shows that majority of respondents’ dairy animals had good health score even though mastitis had a high incidence in majority of respondents’ animals followed by Foot and Mouth Disease and Haemorrhagic septicaemia in the past two years. Majority (94.81%) of the respondents had adopted timely colostrum feeding followed by timely deworming (77.78%) among calf management practices. Mortality rate of calves was about 9 per cent during the preceding two years. The average milk yield, average peak yield, lactation length and dry period of commercial dairy farms were 10.25±2.52 litres, 13.00±2.80 litres, 295±22 days and 3.05±0.59 months respectively. The average age at first calving, average service period, average service / conception and calving interval of commercial dairy farm animals were 2.74±0.47 years, 119.59±13.45days, 2.62±0.58 months and 17.02±1.74 months respectively. Large farmers were having the highest productive and reproductive performance at their dairy farms followed by medium and small dairy farmers. Efforts need to be taken to reduce the disparity in productive and reproductive performance among the dairy farms and enhance productive and reproductive performance of small and medium dairy farm.